Pelatihan Wirausaha Bakery sebagai Solusi Inklusif untuk Masyarakat Usia Produktif di Kota Kediri - Zahra, Tiara Melinda Zahra; Husna, Tsalsabila Nikmatul; Rohmah, Ulil Mawaddatur; Fadhilla, Umi; Khasanah, Ushwatun; Faiza, Nurlaili Adkhi Rizfa (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Bakery Entrepreneurship Training as an Inclusive Solution for Productive Age Communities in Kediri City is an initiative implemented by DINKOP UMTK Kediri City at LPK Kusuma. The aim is to improve culinary skills and entrepreneurial potential for people of productive age. This activity involved 40 participants from various age backgrounds, between 18 and 45 years old. The data collection method uses a mixed questionnaire that evaluates the level of participant satisfaction with the training. The survey results showed that the majority of participants responded positively to the training. They appreciate instructors who provide material well and systematically and encourage participant involvement. However, some participants criticized the training time as being too short and location-related issues. Overall, this training was successful in increasing participants' knowledge and skills in the world of bakery, providing business ideas, and increasing product understanding. This initiative has a positive impact on participants and has the potential for business development in Kediri City.